Gold(I)-catalyzed rearrangement of 3-silyloxy-1,5-enynes: an efficient synthesis of benzo[b]thiophenes, dibenzothiophenes, dibenzofurans, and indole derivatives - Hashmi, A. Stephen K.; Yang, Weibo; Rominger, Frank (Chemistry - a European journal, 2012)
With the IPr ligand (IPr=1,3-bis-(2,6-diisopropylphenyl)imidazol-2-ylidene) on gold(I) excellent yields in the benzanellation of 2-substituted thiophenes, benzothiophenes, pyrroles, benzofurans, and indoles were achieved. The 1-siloxybut-3-ynyl side chains, incorporated in the anellation, are easily accessible by the addition of a propargyl metal reagent to a formyl group and silylation of the alcohol. This conveniently allows an anellation at the position of the formyl group under mild conditions. All reactions involve a 2,3-shift of the side chain in the anellation step and thus, provide an easy access to specific substitution patterns. Only in the case of 2-substituted indoles with their highly nucleophilic 3-position a direct hydroarylation without shift is observed. On the other hand, 3-substituted indoles give the same products as 2-substituted indoles. Then, a 3,2-shift in the indole ring system has to be involved.
Gesehen am 06.09.2018